2000
DOI: 10.1159/000020656
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Restriction Decreases AP-1 Activation after Nephron Reduction in the Rat: Role in the Progression of Renal Lesions

Abstract: Renal hyperplasia and hypertrophy are early events after nephron reduction which precede progressive destruction of the remnant kidney. Restriction of dietary sodium content was shown to reduce renal lesions following nephron reduction. AP-1 is a transcription factor, resulting from heterodimerization of fos and jun proteins, which mediates the effects of mitogenic growth factors. To elucidate the role of AP-1 in growth processes involved in renal deterioration, we evaluated whether restriction of dietary sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…Moreover, several experimental and clinical observations suggest that cell proliferation plays a key role in the destruction of kidneys during chronic disease. First, proliferation of mesangial, tubular, and interstitial cells increases in many renal diseases and correlates with the severity of renal lesions (2)(3)(4)(5). Secondly, we have shown that the development of renal lesions parallels the extent of cell proliferation in two mouse strains (FVB/N and C57Bl6 × DBA2/F1) and in two experimental models (unilateral and subtotal nephrectomy) that respond differently to nephron loss (3,26).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Moreover, several experimental and clinical observations suggest that cell proliferation plays a key role in the destruction of kidneys during chronic disease. First, proliferation of mesangial, tubular, and interstitial cells increases in many renal diseases and correlates with the severity of renal lesions (2)(3)(4)(5). Secondly, we have shown that the development of renal lesions parallels the extent of cell proliferation in two mouse strains (FVB/N and C57Bl6 × DBA2/F1) and in two experimental models (unilateral and subtotal nephrectomy) that respond differently to nephron loss (3,26).…”
Section: Discussionmentioning
confidence: 81%
“…Subtotal nephrectomy induces the expression of c-fos and c-jun genes, cell proliferation, and renal lesions (3). Interfering with the development of renal lesions (either by dietary or by pharmacological modulations) decreases both AP-1 activity and cell proliferation in several experimental models of chronic renal injury (5,(18)(19)(20). Taken together, these results suggest that AP-1 could be a major determinant in the development of renal lesions.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Since EGF is a potent mitogen for renal tubular cells (6, 7) and a relationship between cell proliferation and tubular lesions has been suggested after nephron reduction (40), PCNA immunostaining was performed on kidney sections from transgenic and wild-type animals. In wild-type mice, the number of tubular PCNA-positive cells was slightly higher in remnant kidneys of nephrectomized mice, as compared with shamoperated animals, 8 months after surgery ( Table 2).…”
Section: Subtotal Nephrectomy (Nx)mentioning
confidence: 99%